Reg4 regulates pancreatic regeneration following pancreatitis via modulating the Notch signaling. Issue 11 (26th April 2021) - Dai, Juanjuan; He, Yan; Jiang, Mingjie; Niu, Mengya; Li, Bin; Wu, Zengkai; Bao, Jingpiao; Wen, Li; Wang, Xingpeng; Hu, Guoyong
Abstract: Pancreatic regeneration after acute pancreatitis is critical in the normal restoration of pancreatic exocrine function, the inhibition of which can cause severe complications including pancreatic exocrine insufficiency. However, the regulators of pancreatic regeneration and the underlying mechanisms remain uncovered. Here, using the inducible Tet‐on system, we found that regenerating family member 4 (Reg4) knockdown significantly impaired pancreatic regeneration after pancreatitis. Both acinar‐to‐ductal metaplasia and the resolution of pancreatitis during regeneration were affected by Reg4 knockdown. Further investigations confirmed that Reg4 exerted its function through regulating Notch activation both in vitro and in vivo. Our study revealed Reg4 as a new regulator and potential therapeutic target for pancreatic regeneration. Abstract : Using the inducible Tet‐on system, we found that regenerating family member 4 (Reg4) knockdown significantly impaired pancreatic regeneration after pancreatitis. Both acinar‐to‐ductal metaplasia (ADM) and the resolution of pancreatitis during regeneration were affected by Reg4 knockdown through regulating Notch activation.